2010
DOI: 10.1111/j.1600-0722.2010.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased exposure times of simplified etch‐and‐rinse adhesives on the degradation of resin–dentin bonds and quality of the polymer network

Abstract: One of the reasons for resin-dentin degradation is poor polymerization of the adhesive layer. This study evaluated the effect of prolonged polymerization times on the immediate and 6-month resin-dentin bond strengths, silver nitrate uptake, and polymer quality of etch-and-rinse adhesives. Thirty extracted teeth were obtained, and a flat dentin surface was exposed on each tooth. Adhesives (Adper Single Bond 2 and One Step Plus) were applied to the dentin surface of these teeth and light-cured for 10, 20, or 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
0
28
0
11
Order By: Relevance
“…The second (T peak approximately 360 o C), third (T peak approximately 380 o C) and fourth losses of mass (T peak approximately 400 o C) can be assigned to the decomposition of higher molecular-weight structures, comprising the chain areas formed more intensely by flexible components such as HEMA and TEGDMA for the second and third stages, along with areas of greater rigidity in the fourth stage, with higher prevalence of BIS-GMA and UDMA. 18 Regarding thermal resistance, the groups containing 0.2% filler load showed an increase in thermal resistance while the other concentrations showed no significant changes in this property. This behavior can be explained based on the dispersion of layered nanofillers, since the group with 0.2%, possibly, has an exfoliated morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second (T peak approximately 360 o C), third (T peak approximately 380 o C) and fourth losses of mass (T peak approximately 400 o C) can be assigned to the decomposition of higher molecular-weight structures, comprising the chain areas formed more intensely by flexible components such as HEMA and TEGDMA for the second and third stages, along with areas of greater rigidity in the fourth stage, with higher prevalence of BIS-GMA and UDMA. 18 Regarding thermal resistance, the groups containing 0.2% filler load showed an increase in thermal resistance while the other concentrations showed no significant changes in this property. This behavior can be explained based on the dispersion of layered nanofillers, since the group with 0.2%, possibly, has an exfoliated morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of these polymer systems in a more rigid conformation lead to a less tendency of water sorption, since the reduced flexibility of the polymer networks generates a physical obstacle to the passive diffusion of the solvent through the material. 30 Thus, once the sorption is the primarily responsible for the mechanical strength loss of the adhesive systems because its represent the first stage of degradation of these interfaces by hydrolysis, 31,32 or because the water acts as a plasticizer of these materials, 18,33 the obtaining of these systems with greater rigidity reflects on a larger adhesive stability.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical tests 107,108 have demonstrated that including an extra hydrophobic layer in addition to the self-etching adhesive procedure improves the clinical behavior observed 6, 12, and 24 months after application, mainly in terms of retention of CR restorations performed on Class V non-carious cervical lesions, consecuencia de la disminución de la degradación de unión adhesiva. 90,109,110 Empero, estudios a mayor plazo clínico son necesarios para completar esta información.…”
Section: C Application Of An Additional Hydrophobic Layermentioning
confidence: 99%
“…121 La explicación a este fenómeno podría relacionarse con el hecho de brindar al adhesivo mayor tiempo para la evaporación de sus solventes alcohólicos y agua, especialmente cuando se conoce que la incorporación de agua en los sistemas as a result of lower degradation of adhesive bond. 90,109,110 However, longer-term clinical studies are required to complement this information.…”
Section: D Polimerización Tardía O Evaporación Pasiva Del Solventeunclassified
See 1 more Smart Citation